Fairness, Markets, and Ability to Pay: Evidence from Compensation Executives - Levine, David I. (American Economic Review, 1993)
This paper examines a unique data set based on surveys of 139 compensation executives. Respondents read scenarios describing a hypothetical company and its labor market, and recommended wage changes for several positions. Contrary to some popular theories, differences in unemployment, quit rates, and a company's return of assets led to almost no change in respondents' recommended wage increases. When market wages for closely related occupations diverged, most respondents did not recommend adjusting relative wages within the company; but when the occupations were not closely related (blue vs. white collar), most respondents recommended adjusting relative wages to reflect market forces.